2022
DOI: 10.21931/rb/2022.07.02.35
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Health Beliefs Model-Based Intervention in Changing Substance Use Beliefs among Mosul University Students: A Randomized Controlled Trial

Abstract: Substance use disorders (SUD) are a significant health concern worldwide. Substance abuse is a persistent problem linked to high rates of illness and loss. These issues are also responsible for many healthcare workers and health bills. However, the Substance use problems are associated with capitalize health retrogradation, weakness and death due to impacts and exceed. Throughout Iraq, there is growing concern about the effects of violence and war on drug use. To see how effective HBM-based intervention is at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…And the average age is that most of them are new graduates who have more than one year of service in the job and in the neonatal care units according to the criteria of the study sample. But regarding to the gender of the participants, the majority of them are males given the night shift system in health institutions and the greater reliance on them in that.This study agree with others study in Iraq [10][11][12][13][14][15].In these study and according to the table (2) shows the results for main parts in three tests (pre-test ,post-test1 and post-test2), in terms that a deference's between each part as a(poor) for pre-test and (good) for (post-test1 and post-test2)with slightly different. Were a highly score for Characteristics of newborn baby variable in (pre-test =73.34% poor) , (post-test1=83.34% Good) and (post-test2=80 Good).…”
Section: Resultssupporting
confidence: 94%
“…And the average age is that most of them are new graduates who have more than one year of service in the job and in the neonatal care units according to the criteria of the study sample. But regarding to the gender of the participants, the majority of them are males given the night shift system in health institutions and the greater reliance on them in that.This study agree with others study in Iraq [10][11][12][13][14][15].In these study and according to the table (2) shows the results for main parts in three tests (pre-test ,post-test1 and post-test2), in terms that a deference's between each part as a(poor) for pre-test and (good) for (post-test1 and post-test2)with slightly different. Were a highly score for Characteristics of newborn baby variable in (pre-test =73.34% poor) , (post-test1=83.34% Good) and (post-test2=80 Good).…”
Section: Resultssupporting
confidence: 94%
“…The results are contradictory to those of other studies in which researchers used this model for education. The studies realized by Younis N et al and Fathi M et al showed that all HBM constructs play an important role in adopting preventive behaviors [34,35]. Regarding the mean level of perceived self-efficacy in another study, the main reason for using OTC medications, described by almost two-thirds of mothers, was to preserve their children's lives in emergencies.…”
Section: Discussionmentioning
confidence: 91%
“…The reason for this positive relationship is because the employees started to be self-efficacy and have a relationship with friends and colleagues working inside the University. The study 28,29,30 . confirmed a strong correlation between self-efficacy, social support, and activity-related effectiveness.…”
Section: Discussionmentioning
confidence: 99%